Shenmai Injection enhances short-term outcomes in ischemic stroke patients after thrombolysis via AMPKα1 - Jing Wu; Zhonghao Li; Xiaoke Dong; Jinmin Liu; Le Wang (Frontiers in Pharmacology)
BackgroundShenmai Injection (SMI), a traditional Chinese medicine with nourishing properties, has been explored for its therapeutic effects in ischemic stroke (IS). This study aimed to evaluate the protective effects of SMI in patients with IS who received intravenous thrombolysis and to elucidate its potential molecular mechanisms through laboratory investigations.MethodsPatients with IS were randomized to receive either SMI or a placebo for 10 days within 12 h post-intravenous thrombolysis. Clinical efficacy and safety were assessed. An IS cell model was induced using H2O2, followed by treatment with SMI to explore its therapeutic effects and underlying mechanisms.ResultsThe modified Rankin Scale (mRS) score at 30 days was significantly lower in the SMI group (n = 35) compared to the placebo group (n = 35), indicating improved functional outcomes. No significant difference was observed in NIHSS scores between the groups. Adverse events and biochemical indices showed no significant differences, confirming the safety of SMI. In the H2O2-induced cell model, SMI enhanced cell viability, reduced apoptosis, and decreased the levels of malondialdehyde (MDA) and reactive oxygen species (ROS). It also improved ATP content and mitochondrial membrane potential. Mechanistic studies revealed that these protective effects were partially mediated through the AMPKα1.ConclusionSMI significantly improves short-term outcomes in IS patients treated with rt-PA thrombolysis. Its protective effects are likely mediated through the AMPKα1, highlighting its potential as an adjunctive therapy for IS.